A transparent polyvinylidene fluoride–hexafluoropropylene composite film with enhanced energy conversion and energy preservation performance. Issue 4 (24th May 2021) - Wang, Xin; Wang, Wenjiang; Tong, Wangshu; Zhang, Yihe; Wang, Zhihao; Ma, Yuan; An, Qi
Abstract: Integrated energy‐generating and storage films are able to convert mechanical force into stored electrical energy, with the potential for use in self‐powered wearable electronics and flexible energy supplies. The development of a transparent metal salt/polyvinylidene fluoride–hexafluoropropylene composite film is reported that possesses excellent piezoelectric and dielectric properties and has the potential to be employed as an energy‐generating and preserving integrated film. The effects of the type of the metal salt and its content on the dielectric properties, d33 value, open circuit voltage, and holding time of the composite films were investigated. Owing to the presence of pure water, the β ‐phase composition and polarization of the film are increased, leading to improved energy conversion properties. Most important, the prepared film exhibits excellent light transmittance. This film, which possesses both good electrical and transparent properties, has the potential for use as a flexible energy supplier, particularly for photovoltaic devices.